Performance of Kalung Cricket (Gryllus bimaculatus) Fed with a Combination of Concentrate and Cassava Leaves - A. Sunyoto; Endrawati, Y. C.; D. A. Astuti; A. M. Fuah; H. Nuraini; V. A. Mendrofa; A. K. Islami; Winarno (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
Crickets are a promising alternative source of animal protein due to their high levels of amino acids, fatty acids, and protein (61.58%). These nutrients have applications in the pharmaceutical industry, human food, bird feed, and as a substitute for livestock feed, particularly in the form of cricket flour. The Kalung cricket (Gryllus bimaculatus) is notable for its rapid growth rate and efficient feed conversion. This study aimed to evaluate the effects of diets combining concentrate with cassava leaves of different maturities on the performance of Kalung crickets (Gryllus bimaculatus). A completely randomized design (CRD) was employed, consisting of three treatments with five replications each. The treatments were R1= concentrate+young cassava leaves, R2= concentrate+mature cassava leaves, R3= concentrate+cassava leaf stems, with a combination ratio of 1:1.5. The parameters observed include feed consumption, body weight gain, egg production, feed conversion, mortality, and income over feed cost (IOFC). The results showed that no significant differences among treatments in feed intake, weight gain, and mortality. However, significant differences were observed in egg production (0.022±0.011 g/individu/day) and feed conversion (1,88±0.95) with the R1 treatment showing the most favorable results. A diet combining concentrate with young cassava leaves significantly improves the reproductive performance and feed efficiency of Kalung crickets. This combination is recommended for enhancing productivity in Gryllus bimaculatus farming systems.